2020
DOI: 10.1124/jpet.119.264887
|View full text |Cite
|
Sign up to set email alerts
|

eNOS-Nitric Oxide System Contributes to a Novel Antiatherogenic Effect of Leonurine via Inflammation Inhibition and Plaque Stabilization

Abstract: Leonurine (LEO) is a bioactive small molecular compound that has protective effects on the cardiovascular system. It prevents the early progression of atherosclerosis, however, it is not clear whether LEO is effective for plaque stability. A novel mouse atherosclerosis model involving tandem stenosis (TS) of the right carotid artery combined with western diet (WD) feeding was used. ApoE-/mice were fed with a WD and received LEO administration daily for 13 weeks. TS was introduced 6 weeks after the onset of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Nitric oxide is a key signaling molecule in endothelium to act as vasodilator factor, generated by nitric oxide synthase (NOS) ( 78 ). Endothelial production of NO can inhibit multiple events during AS, such as inhibiting ECs activation, macrophage infiltration ( 79 ), foam cell formation/migration ( 80 ), platelet aggregation ( 81 ), inflammation ( 82 ), thrombosis ( 83 ), vascular wall remodeling ( 84 ), and mediating vasodilation ( 85 ). The mechanism of Hcy disturbance of NO synthesis is relatively complex, asymmetric dimethylarginine (ADMA) plays an important role in it, which is an endogenous inhibitor of NOS.…”
Section: Mechanism Of Endothelial Injury By Homocysteinementioning
confidence: 99%
“…Nitric oxide is a key signaling molecule in endothelium to act as vasodilator factor, generated by nitric oxide synthase (NOS) ( 78 ). Endothelial production of NO can inhibit multiple events during AS, such as inhibiting ECs activation, macrophage infiltration ( 79 ), foam cell formation/migration ( 80 ), platelet aggregation ( 81 ), inflammation ( 82 ), thrombosis ( 83 ), vascular wall remodeling ( 84 ), and mediating vasodilation ( 85 ). The mechanism of Hcy disturbance of NO synthesis is relatively complex, asymmetric dimethylarginine (ADMA) plays an important role in it, which is an endogenous inhibitor of NOS.…”
Section: Mechanism Of Endothelial Injury By Homocysteinementioning
confidence: 99%
“…In addition to specific immunomodulatory approaches, derivatives of traditional medicines have also been explored in the TS model. The active alkaloid leonurine, an extract from the traditional Chinese medicine Herba leonuri, has been demonstrated to have protective effects in models of CVD (Ning et al, 2020). Using the TS model, Ning et al demonstrated that leonurine treatment increased plaque stability and observed increased collagen content and fibrous cap thickness and decreased inflammation.…”
Section: Biological and Translational Insights From The Ts Modelmentioning
confidence: 99%
“…[48] SCM198 [4-guanidino-n-butyl syringate, Figure 3B] is a chemically synthesized compound that exhibits cardioprotective effects in myocardial infarction models [49] as well as neuroprotective effects on middle cerebral artery occluded rats. [50] Pretreatment with SCM198 (0.1, 1, and 10 mM) significantly increased SOD activity, ameliorated intracellular ROS generation, prevented the dissipation of mitochondrial membrane potential, decreased apoptotic cell death, downregulated Bax, and upregulated Bcl-2 mRNA and protein levels compared with those in 6-OHDA damaged cells. Intragastric administration of SCM198 at 18 or 60 mg/kg/day for 4 weeks significantly ameliorated apomorphine-induced contralateral rotations in 6-OHDA-lesioned rats.…”
Section: Antioxidant Compounds In Experimental Models Of Pdmentioning
confidence: 88%